Nova epoha / New Epoch: Novi (već viđeni) ratovi / New (already seen) Wars - Arnaut-Haseljić, Meldijana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
The text is a review of a book Hva er krig (What is War) by Øyvind Østerud (translated from Norwegian by Rasim Muratović, Sarajevo, 2016.).